Peril at King's Creek : a Felicity mystery - Jones, Elizabeth McDavid, 1958- (Middleton, WI : Pleasant, 2006)
In 1776, Penny is concerned that the British Army will steal her horse and burn her family's plantation.
"American girl."
"American Girl mysteries".
Includes historical information about the Revolutionary War.
009-up.
Accelerated Reader AR
Keywords: United States -- History -- Revolution, 1775-1783 -- Juvenile fiction; Historical fiction; Mystery fiction